3D RGO frameworks wrapped hollow spherical SnO2-Fe2O3 mesoporous nano-shells: fabrication, characterization and lithium storage properties. (1st June 2016) - Zhao, Bo; Xu, Yi-Tao; Huang, Sheng-Yun; Zhang, Kai; Yuen, Matthew M.F.; Xu, Jian-Bin; Fu, Xian-Zhu; Sun, Rong; Wong, Ching-Ping
Abstract: Three-dimensional (3D) reduced graphene oxide (RGO) frameworks confined hollow spherical SnO2 -Fe2 O3 @RGO nano-shells (3D h-SnO2 -Fe2 O3 @RGO) are successfully obtained by hydrothermal reduction of h-SnO2 -Fe2 O3 @GO in graphene oxide (GO) suspension. As anode materials for lithium-ion batteries (LIBs), the novel 3D h-SnO2 -Fe2 O3 @RGO architectures demonstrate great improvement in cycling performance (∼830 mAh g −1 after 100 cycles at 200 mA g −1 ) and rate capability (∼550 mAh g −1 at 1000 mA g −1 for 10 cycles) over that of hollow SnO2 spheres (h-SnO2 ), h-SnO2 -Fe2 O3, and 3D RGO frameworks wrapped hollow spherical SnO2 @RGO nano-shells (3D h-SnO2 @RGO). The 3D porous frameworks and coating graphene nano-shells serve as efficient electron and ion conductive networks as well as buffer for the large volume variation of hollow SnO2 -Fe2 O3 during cycling. Moreover, the hollow spherical metal oxide mesoporous nano-shells could enlarge the surface area, retard the volume change, prevent aggregation of nanosized active materials and graphene nanosheets.